Optimizing the conditions for performing experiments on Newton's second law of motion - Galvez, Francisco L. 1950-
If great stress is made on the laboratory as a major instructional tool, there should be less use of illustrative types of exercises. In order that student experiments yield usable data from which relationships can be derived, what may be necessary only is for the teacher to know the factors which cause difficulties and to specify as competely as possible the conditions for performing the experiments. The problem of the study was to determine such factors and conditions.